Implementation of the Adiwiyata Program in Enhancing Environmental Awareness - Arifah, Siti; Nurkolis, Nurkolis; Muhtarom, Muhtarom (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This research is motivated by global and local environmental degradation and the challenge of strengthening students’ awareness of environmental preservation in schools. This study aims to analyze and describe the planning, implementation, and evaluation of the Adiwiyata Program in fostering students’ environmental care character at Sambongsari 2 Public Elementary School, Sambongsari Village, Weleri District, Kendal Regency, Central Java, Indonesia. This study employed a descriptive qualitative approach with a case study design. The research subjects consisted of the principal, Adiwiyata implementation team, teachers, school committee, students, and janitors. Data were collected through structured observations, in-depth interviews, and documentation. Data analysis used the interactive model of Miles, Huberman, and Saldaña, consisting of data collection, data condensation, data display, and conclusion drawing. Data validity was established through source and technique triangulation. The findings show that: (1) the planning stage was conducted systematically and participatively by involving stakeholders through environmental reviews and environmental action plans; (2) the implementation stage was realized through environmentally friendly policies integrated into the school vision and mission and the School Curriculum (KSP), budget allocation of less than 20% in the School Activity and Budget Plan (RKAS), integration of environmental content through the “natural infusion” method in teaching modules, and optimization of ecological facilities, including a greenhouse, TOGA garden, mini-forest, and 3R waste management system; and (3) evaluation was conducted periodically through quarterly policy monitoring and monthly clinical supervision in the Teacher Working Group (KKG). Differences in students’ environmental behavior between school and home were addressed through waste recycling training for parents. This study contributes to ecological character education literature and provides practical insights for sustainable school quality improvement.